PM.22 The Role of VEGF165B in Trophoblast Survival – Implications For Pre-Eclampsia Pathophysiology. (26th April 2013) - Bills, VL; Bates, DO; Soothill, PW; Overton, T
Abstract : It is widely accepted that the pathophysiological foundations of pre-eclampsia are laid down in the first trimester, with inadequate invasion of placental trophoblasts into maternal spiral arteries of the uterus, resulting in defective arterial remodelling. The angiogenic VEGF family of glycoproteins are expressed in first trimester trophoblasts and are important factors in placental development, which occurs in a hypoxic (<2% O2 ) environment up to 10–12 weeks and normoxia (>20% O2 ) thereafter. First trimester VEGF165 b levels are low in women destined to later develop pre-eclampsia, so we investigated whether VEGF165 b plays a role in early trophoblast survival and therefore pre-eclampsia pathophysiology. Trophoblast cells were cultured in hypoxic and normoxic environments, in the absence and presence of VEGF165 b and a VEGF165 b blocking antibody clone 56–1. Cell survival was studied via cytotoxicity experiments. Production of VEGF165 b by trophoblasts was determined via enzyme linked immunoassay (ELISA). VEGF165 b production by trophoblasts was increased in response to hypoxia (hypoxia: 1812 ± 33 pg/ml vs. normoxia: 1407 ± 95 pg/ml, unpaired t test, p = 0.016), and inhibition of VEGF165 b increased trophoblast death (from a baseline of 17.8 ± 2.6% to 30.8 ± 2.7%, p = 0.0068). In normoxic conditions VEGF165 b decreased trophoblast death in a dose dependent manner from 33.6% ± 0.6 (control) to 29.2% ± 0.9 with 40 ng/ml VEGF165 b to 24.2% ± 3.5 with 80 ng/ml VEGF165 b, One way ANOVA, p = 0.0019, Dunnett's Multiple Comparison Test. These findings suggest that VEGF165 b deficiency is associated with trophoblast death, VEGF165 b supplementation with trophoblast survival This has implications for pre-eclampsia pathophysiology.